2019
DOI: 10.1080/21655979.2019.1613103
|View full text |Cite
|
Sign up to set email alerts
|

Tetramethylpyrazine (TMP) protects rats against acute pancreatitis through NF-κB pathway

Abstract: Acute pancreatitis (AP) is a digestive disease characterized by pancreatic inflammation. Tetramethylpyrazine (TMP) has been effectively used to ameliorate the damage on intestinal mucosa injury in rats with acute necrotizing pancreatitis (ANP). We aim to study the protective effect of TMP on caerulein-induced AP and to explore the possible mechanism. The mice randomized into control and different experimental groups. AP was induced in mice by 6-hourly intraperitoneal (i.p) injections of caerulein (50 μg/kg at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 45 publications
(43 reference statements)
2
8
0
Order By: Relevance
“…Interestingly, macrophage infiltration was significantly reduced after heparin treatment, and the expression of inflammatory factors TNF-α, IL-6, and IL-1β was significantly decreased. This result is similar to the findings of Chen et al [ 34 ]. They found that Tetramethylpyrazine reduced the severity of AP by decreasing the levels of pro-inflammatory factors TNF-α and IL-6.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, macrophage infiltration was significantly reduced after heparin treatment, and the expression of inflammatory factors TNF-α, IL-6, and IL-1β was significantly decreased. This result is similar to the findings of Chen et al [ 34 ]. They found that Tetramethylpyrazine reduced the severity of AP by decreasing the levels of pro-inflammatory factors TNF-α and IL-6.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have also reported the ability of rupatadine to inhibit NF-κB activity and TNF-α expression (Mullol et al 2008;Queralt et al 2000). We assume that the inhibition of the NF-κB/TNF-α pathway mediates the therapeutic effect of rupatadine against AP consistent with (Chen et al 2019). The increased IL-1β production in the AP group was consistent with the finding of (Wu et al 2021) who reported that IL-1β production by activated neutrophils causes more tissue damage during AP progression.…”
Section: R a F Tsupporting
confidence: 70%
“…Accumulating evidence demonstrates that cell apoptosis represents a favorable response during the course of SAP [11][12][13][14]. Apoptosis and necrosis, two forms of cell death, are key pathological responses of SAP.…”
Section: Introductionmentioning
confidence: 99%